A successful case of extracorporeal membrane oxygenation treatment for intractable pneumothorax in a patient with COVID‐19. Issue 1 (9th December 2020) - Nakatsutsumi, Keita; Sekiya, Kosuke; Urushibata, Nao; Hosoi, Marie; Arai, Hirokuni; Nagaoka, Eiki; Fujiwara, Tatsuki; Morishita, Koji; Aiboshi, Junichi; Otomo, Yasuhiro
Abstract : Background: Some patients with coronavirus disease 2019 (COVID‐19) develop pneumothorax. Tube thoracotomy and bulla resection could generate aerosols and cause virus transmission; the optimal treatment strategy remains unclear. Case Presentation: A 57‐year‐old male was transferred as a severe COVID‐19 pneumonia case. On the 16th day after admission, the patient's respiratory condition deteriorated, and the chest X‐ray revealed the presence of severe right‐sided pneumothorax. A chest drain was immediately inserted; however, a significant air leak continued, and severe ventilator settings were required. Thus, veno‐venous extracorporeal membrane oxygenation (VV‐ECMO) treatment was initiated to allow the lungs to rest. After 10 days of lung‐protective ventilation, the patient was weaned from ECMO and the chest drain was removed on the following day with no major comorbidities. Conclusion: The combination of ECMO with lung rest strategy could be a treatment option for intractable pneumothorax with COVID‐19 to avoid unnecessary surgical procedures and aerosol generation. Abstract : The combination of extracorporeal membrane oxygenation with lung‐protective ventilation strategies could be a potential treatment option for intractable pneumothorax with coronavirus disease 2019 (COVID‐19) to avoid unnecessary surgical procedures and aerosol generation.